New species of Pararhagadochir Davis, 1940 (Insecta: Embioptera: Scelembiidae) from Brazil - Salvatierra, Lidianne (Zootaxa, 2020)
A new species of Pararhagadochir Davis, 1940 is described from the State of Tocantins, Brazil. Pararhagadochir castaneus sp. nov. differs from its congeners by relatively smaller size, elongated forewings, body uniformly chestnut-brown, submentum inflexed and strongly sclerotized, outer tip of 10Lp with both sclerotized and membranous areas and Cu vein unforked. An identification key to all species of Pararhagadochir and a short identification key to the Brazilian species are provided.